Investigation of Spatter Trajectories in an SLM Build Chamber under Argon Gas Flow - Awad B. S. Alquaity; Bekir S. Yilbas (Metals, 2022)
Spatter particles ejected from the melt pool during selective laser melting processes can get redeposited on the build plate region and impact final part quality. Although an inert gas flow is used to purge the spattered particles away from the build plate region, some of the spatter particles get redeposited on the plate region leading to increased porosity and surface roughness. In this regard, the current study focuses on the numerical modeling of the interactions between the inert gas flow and spatter particles by using the discrete phase model. A Renishaw AM250 build chamber is used as the base geometry and the flow field within the build chamber is evaluated for various inert gas flow rates and nozzle diameters of 6 mm and 12 mm. For the first time, spatter trajectories are tracked at specific spatter diameters and ejection angles to pinpoint the influence of drag and gravitational forces on the evolution of spatter trajectories. The findings reveal that the spatter particles between 120 and 180 μm diameter travel beyond the build plate only at specific gas ejection angles and gas flow rates (≥750 L/min). Reducing the nozzle diameter to 6 mm increases the inert gas flow velocity in the build region and enhances the range of spatter particles. New correlations are proposed to relate the range of particles and inert gas flow rates, which can be used to identify the spatter diameters, ejection angles, and inert gas flow rates required to transport the particles beyond the sensitive build plate region.